Kidney outcomes with SGLT2is for type 2 diabetes patients: does background treatment with metformin or RASis matter? - Chong, Kah Suan; Chang, Yi-Hsin; Lin, Meng-Hsuan; Hsu, Chien-Ning; Wang, Chi-Chuan; Wang, Chih-Yuan; Huang, Yun-Lin; Lin, Fang-Ju; Ou, Huang-Tz (Frontiers in Endocrinology, 2024)
There is a lack of real-world evidence regarding the impact of concomitant metformin and renin-angiotensin system inhibitors (RASis) on sodium-glucose cotransporter-2 inhibitor (SGLT2i)-associated kidney outcomes. This study was aimed to investigate whether SGLT2i-associated kidney outcomes were modified by the concomitant use of metformin or RASis in patients with type 2 diabetes.Methods: SGLT2i users were identified from three electronic health record databases during May 2016 and December 2017 and categorized into those with and without concomitant use of metformin or RASis. Propensity score matching was performed to minimize baseline differences between groups. Study outcomes were mean estimated glomerular filtration rate (eGFR) change and time to 30%, 40%, and 50% eGFR reductions. A meta-analysis was performed to combine the estimates across databases.Results: After matching, there were 6,625 and 3,260 SGLT2i users with and without metformin, and 6,654 and 2,746 SGLT2i users with and without RASis, respectively. The eGFR dip was similar in SGLT2i users with and without metformin therapy, but was greater in SGLT2i users with RASis compared to those without RASis. Neither metformin nor RASi use had a significant effect on SGLT2i-associated eGFR reductions, as evidenced by the hazard ratios (95% CIs) of 30% eGFR reductions for SGLT2is with versus without metformin/RASis, namely 1.02 (0.87-1.20)/1.09 (0.92-1.31). Such findings were also observed in the outcomes of 40% and 50% eGFR reductions.Conclusions: Using metformin or RASis did not modify SGLT2i-associated kidney outcomes in type 2 diabetes.